Analisis Daya Dukung Pondasi Spun Pile Dievaluasi Dengan Kalendering Dan PDA - Fadilla, Rahma Nur; Pradiptiya, Andikanoza (Indonesian Society of Applied Science, 2022)
In a bridge construction project, there are two types of structures, namely the superstructure and the substructure. The foundation is part of the substructure that functions as the main support and the most important part that greatly affects the stability of the building above it. In foundation design, it is required to calculate the bearing capacity. The bearing capacity of the foundation can be predicted based on soil investigation data which compared by actual field dynamic test data. Dynamic test is carried out to determine the actual bearing capacity after pile installation. This research aims to predict of spun pile bearing capacity and settlement based on N-SPT data, then evaluated by dynamic test (PDA and calendering) at “X” Toll Road Construction Project. Moreover, an evaluation of the axial bearing capacity of single and group piles will be carried out against the workloads. The results shows that prediction of the bearing capacity closest to the PDA data using Luciano Decourt Method (1987) around 309.45 tons with a difference of 4.20% each other. Calendering analysis by Gates Method found that 301.46 tons with a difference of 50.8% against the prediction. The prediction of immediate settlement is obtained of 26.79 mm smaller than PDA result and a difference of 13.30%. The results of the evaluation of the axial bearing capacity of single and group piles against workloads show that both the predicted and actual (PDA and calendering) bearing capacity is greater than the workload.